ANGKUL-ANGKUL ARCHITECTURAL TRANSFORMATION ALONG WITH THE DEVELOPMENT OF TOURISM IN SANUR, BALI - Tantra, I Gusti Agung Bagus Parameswara (Jurnal Arsitektur ZONASI, 2023)
Traditional Balinese Architecture (ATB) is one of the architectural styles of the archipelago that continues to grow and develop over time. Globalization has undoubtedly had a significant impact on this development, which has resulted in rapid changes in various areas. In the Balinese context, the change in the shape of traditional Balinese architecture is closely related to the development of tourism. The Bali Island, which became a meeting point for tourists from some countries, resulted in many transformations in the concept, shape, and function of Balinese architecture due to foreign influences. One of the physical forms of Balinese architecture that undergo many transformations is the Angkul-Angkul. Transformation in Angkul-Angkul is generally easy to find in villages closely related to Bali's tourism sector. Sanur Village was chosen as an observation location because it is in an area that became the starting point for tourism development on Bali Island. Sanur is one of the tourist villages in Bali where the transformation of Angkul-Angkul is very easy to find through villa buildings and hotels in the village. Angkul-Angkul now not only serves as the main entrance to the building for its residents. But, it also develops into access to vehicle circulation to form the identity of the building. The transformation of Angkul-Angkul is strongly influenced by many things, including the characteristics of the location where the Angkul-Angkul stands, the function accommodated by it, the development of modern material technology, and various parties involved in it, such as architects or owners of the Angkul-Angkul building. The method carried out in researching the transformation of Angkul-Angkul in Sanur village was through direct observation and assessing several aspects that had changed both in terms of material and shape and function. Some theories related to the transformation of the Angkul-Angkul form were also used as a foundation in assessing changes that occurred between the realization of traditional Angkul-Angkul and the realization of Angkul-Angkul after transforming. Through this research, the author identified the extent of the influence exerted by tourism actors on many transformations in the shape and function of Angkul-Angkul that occur in Bali, especially in Sanur village.Keywords: transformation; angkul-angkul; Traditional Balinese Architecture; Sanur;